Pengaruh kualitas pelayanan pemandu museum terhadap kepuasan pengunjung di Museum Geologi Bandung - Saputra, Ginanjar Wira; Kurniawati, Kurniawati; Eka Putri, Tiyana (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to examine the effect of the service quality of the museum guides on visitor satisfaction at the Bandung geological museum. The method used is descriptive method with a quantitative approach, while the data collection technique is carried out by distributing questionnaires to a number of museum visitor, literature study, observation, and interviews. The results indicate that Quality of Service Guides affects significantly on visitor satisfaction. it is proven that there is a positive and significant relationship between variable X (Service Quality) and variable Y (Visitor Satisfaction). Meanwhile, based on the coefficient of determination, it is known that the achievement of the ability of variable X has an effect on variable Y, namely 56.40%, while the rest is influenced by other variables not examined in this study. Based on the research results, it can be stated that the variable quality of museum guide service and visitor satisfaction variables are good. Some suggestions that the researchers convey are to cultivate 5S smiles, greetings, greetings, courtesy and courtesy, so that visitors to the geology museum feel satisfied and comfortable getting services from guides at the Bandung Geological Museum.